Implementasi Graphic Rating Scale Dalam Menentukan Prioritas Indent Motor Pada Dealer Sepeda Motor: Implementation of the Graphic Rating Scale in Determining Motorcycle Indent Priorities at Motorcycle Dealers - Riandhita Arief Permana, Denny; Fahrulrozi, Muhamad; Ismono, Ahlan; Ningrum, Rahmadani Tyas (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2024)
PT Cheger Motor is an authorized dealer that provides engine maintenance and spare part sales for Honda motorcycle, located in South Tangerang. Sales is the main focus of business process in this company, that being the case, there are two types of sales methods, regular and indent. Indent method were used should the motorcycle ordered by the customer is not readily available, therefore the customer should order in advance. In practice, the existing information system doesn’t have the feature to manage and store SPK (Surat Pemesanan Kendaraan - Vehicle Order Letter). The process of generating an indent inquiries are done manually with physical ledger, and those orders are followed up manually, one by one via WhatsApp. This issue increases the occurrence of booking delays, damage, loss, and redundancy of indent data. In addition, a feature is needed to set up an indent queue to reduce delays in the delivery of purchased vehicles to reduce the rate of order cancellation. This research aims to develop an integrated information system to store, manage and calculate the priority value of the indent queue in carrying out the indent process. To get the result of the priority value, there are few steps needed, first we should collect sales and indent data, then determine the weight of each criterion, and apply an appropriate calculation methods. Therefore, the Graphic Rating Scale method was chosen to assess the priority point for each transaction, to properly arrange the order priority based on the related criterion. Keywords: Indent, Waterfall, Graphic Rating Scale, Google Data Studio